Herbs in exercise and sports - Chee, K. C.; Ayu, S. M.; Foong, K. O. (Journal of Physiological Anthropology, 2012)
The use of herbs as ergogenic aids in exercise and sport is not novel. Ginseng, caffeine, ma huang (also called 'Chinese ephedra'), ephedrine and a combination of both caffeine and ephedrine are the most popular herbs used in exercise and sports. It is believed that these herbs have an ergogenic effect and thus help to improve physical performance. Numerous studies have been conducted to investigate the effects of these herbs on exercise performance. Recently, researchers have also investigated the effects of Eurycoma longifolia Jack on endurance cycling and running performance. These investigators have reported no significant improvement in either cycling or running endurance after supplementation with this herb. As the number of studies in this area is still small, more studies should be conducted to evaluate and substantiate the effects of this herb on sports and exercise performance. For instance, future research on any herbs should take the following factors into consideration: dosage, supplementation period and a larger sample size.